Reading architectural history - Arnold, Dana; ebrary, Inc. (London : Routledge, Taylor & Francis Group, 2002)
Architectural history is more than just the study of buildings. Architecture of the past and present remains an essential emblem of a distinctive social system and set of cultural values and as a result it has been the subject of study of a variety of disciplines. But what is architectural history and how should we read it? Reading Architectural History examines the historiographic and socio/cultural implications of the mapping of British architectural history with particular reference to eighteenth - and nineteenth-century Britain. Discursive essays consider a range of writings from biographical and social histories to visual surveys and guidebooks to examine the narrative structures of histories of architecture and their impact on perception adn understanding of the architecture of the past. Alongside this, each chapter cites canonical histories juxtaposed with a range of social and cultural theorists, to reveal that these writings are richer than we have perhaps recognised and that architectural production in this period can in interrogated in the same way as that from more recent past - and can be read in a variety of ways. The essays and texts combine to form an essential course reader for methods and critical approached to architectural history, and more generally as examples of the kind of evidence used in the formation of architectural histories, while also offering a thematic introduction to architecture in Britain and its social and cultural meaning.
Reading the past : what is architectural history? What is history? / EH Carr ; The fictions of factual representation / Hayden White -- The authority of the author : biography and the reconstruction of the canon. Biographical dictionary / Sir Howard Colvin ; What is an author? / Michel Foucault -- On classical ground : histories of style. Architecture in Britain, 1530-1830 / Sir John Summerson ; Art history and class struggle / Nicos Hadjinicolaou -- A class performance : social histories of architecture. Life in the English country house / Mark Girouard ; In search of cultural history / EH Gombrich --The illusion of inclusion : the guidebook and historic architecture. The buildings of England / Sir Nikolaus Pevsner ; The Blue guide / Roland Barthes -- Reading architectural herstories : the discourses of gender. Sexism and the star system in architecture / Denise Scott Brown ; Planning and representation in the early modern country house / Alice T Friedman
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: historiografie umění; dějiny architektury; architektura -- Velká Británie -- 18.-19. století; art historiography; history of architecture; architecture -- Great Britain -- 18th-19th centuries; eseje; antologie; e-knihy online; essays; anthology; e-books online